(untitled) (Conferencea, 2022)
In the article, we can find out what spiritual and moral issues are of great importance during the period of Eastern Awakening. The article mainly describes the thoughts, moral oppositions of the scientists who lived and invented in the IX-XII centuries and the contents of the works they wrote. This in turn helps to become a qualified personnel in the field of pedagogy at the present time